Analysis of discharge consistency and performance of a sugarcane billet planter with side-conveyer concept - Titinai Thienyaem; Khwantri Saengprachatanarug; Masami Ueno; Taira Eizo (KKU Engineering Journal, 2016)
Sugarcane is an important economic crop of Okinawa Prefecture. The sugarcane billet planter has been widely used in Okinawa due to high labor costs and planting time limits. Most of them were powered by hydraulic systems to avoid ground wheel drive problems when working under high moisture heavy clay conditions. This study aimed to evaluate the performance and discharge consistency of the sugarcane billet planter, YABIKU B600, operated in Minami Daito Island, Okinawa Prefecture. The Ni28 cultivar seed cane was harvested and chopped to an average length of 21.8 cm by Austoft TM2008 harvester. The field experiment was done with 3 replications. A video camera with GPS logger was positioned over the hopper of the planter during the tests to examine the performance and planting consistency of the planter. The numbers of discharged billets at each frame were recorded to calculate the discharge index or planting rate. Moreover, the speed, GPS position and time of each activity were collected to obtain the field capacity and field efficiency of the planter. The results showed that the average traveling speed of the planter was 0.97 m/s. The field capacity was 0.24 ha/hr with a field efficiency of 45.66%. The average discharge index was 7.2 billet/m. Considering a discharge index range of 8-10 billet/m, the precision index averaged 24.63%.